From shadow schools to public schools: Insights from substitute EFL teachers’ identity conflicts - Du, Chao; Ahmad, Norhakimah Khaiessa; Jamil, Halimah binti (Elsevier, 2025)
Research on EFL teacher identity concentrates on identity conflicts from tensions between personal identity pressure and contextual pressures. Limited research considers identity conflicts of marginalized substitute EFL teachers with shadow school teaching experience during their career transition. Adopting a qualitative case study approach, this research explores identity conflicts of primary school substitute EFL teachers from shadow schools to public schools in China. Data were collected from semi-structured interviews and classroom observations. The Dynamic Systems Model of Role Identity is used as the theoretical framework. Four identity conflicts were identified when the participants talked about their administrative working experience, career goals, pedagogical decisions and actions as well as teacher-student relationships. These conflicts influenced the participants' identity construction through the “conflict-emotion-agency-identity (transformation or deconstruction)” process, influenced by the participants’ career adaptability, motivation and continuous learning. Practical implications are provided for school administrations in scientific management and the professional development of substitute teachers.